Strategi Pemasaran Bank Syari’ah Berbasis Digital Fintech terhadap Pelayanan Nasabah Bank BTN Syariah Bengkulu - Sintia, Selfi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This research aims to examine the marketing strategy implemented by Bank Tabungan Negara (BTN) Syariah Bengkulu in implementing digital fintech services and the extent to which sharia values are integrated into it. Using a qualitative approach, this study found that BTN Syariah Bengkulu has succeeded in adopting a comprehensive marketing strategy, including market segmentation based on demographics, geography and psychography, as well as strengthening promotions through digital services such as BTNS Mobile, Virtual Account and QRIS. The results show a high level of customer satisfaction with the practicality and security of digital services, despite facing challenges such as gaps in technological understanding among elderly customers and technical obstacles. The Bank proactively addresses these obstacles through education and system improvements. In addition, the implementation of sharia values, especially in the brand, service and process aspects, is the main foundation that strengthens the bank's identity. Consistency in maintaining the principles of shidq (honesty), ′adl (justice) and maslahah (kindness) not only makes BTN Syariah Bengkulu modern and competitive, but also confirms its position as a banking institution that adheres to Islamic principles.